ON THE ISSUE OF ENSURING THE OPERABILITY OF FREIGHT CAR AXLE BOXES - Martynov, І.; Trufanova, А.; Shovkun, V.; Lytovchenko, O.; Dmytrenko, M.; Balashov, O. (Municipal economy of cities. Series: «Economy science», 2024)
The article is devoted to analysing the reliability of freight car axle boxes. Wheelsets and axle boxes are especially important for ensuring the traffic safety of trains. The study examined cases of cars uncoupling from a train along the route due to technical faults resulting in delays in train movement. The analysis covered the period of 1995–2023. It found that failures of car axle boxes and automatic brakes predominated. After a significant decrease from 2000–2014, the number of roller axle box failures in recent years fluctuated at 30% of the total number of uncouplings. The analysis obtained a dependency for the change in car detachments due to roller bearing failures, calculated per 1,000 cars in the operating fleet. Despite fluctuations in the number of railcars, the safety level of operations in recent years remained virtually at the same level. The study highlighted that excessive heating accompanies damage in the elements of the axle box unit. It considered methods for detecting possible failures and their advantages and disadvantages. The authors identified the primary causes of axle box component failures. Cylindrical bearings and end mountings remain the most dangerous for failure probability. We demonstrated that the axle box design with cylindrical bearings has a fundamental flaw. Axial forces are perceived through the rolling friction of the ends of the rollers against the ring flanges, leading to the formation of ‘chevron’ scratches and dents on the roller ends, which are stress concentrators. The study established that the surface of the axle box housing is constantly in contact with the side frame of the freight car bogie and wears out. It results in pinching of the axle box body and contributes to the appearance of additional permanent forces acting on the axle box assembly. The end-bearing mounts are weakened and destroyed. Skewed rollers in the bearings cause fatigue failure of the rolling races. It leads to increased heating of the axle box assemblies and uncoupling of the car. A promising direction is the improvement of axle box bodies.